Green coconut water administration potentiates positive correlation between reproductive organs' weight and sex hormone profile in flutamide induced androgen perturbation in male prepubertal Wistar rats - Abdulkareem Temitayo Olayinka; Airat Bakare; Ademola Oremosu; Ahmad Tijani; Adedeji Enitan Adetunji (Elsevier, 2024)
Background: The reproductive system is the chief precursor system, whose germ cell activities lead to the emergence of other systems, that work synergistically to maintain body homeostasis. Androgen plays an integral role in the development and optimal functioning of the male reproductive organs. Green coconut water (Yezi shui) is a natural, thirst quenching and therapeutic beverage consumed both recreationally and medicinally amidst the Chinese populace for its diverse health benefits. Aim and objectives: This study was aimed at investigating the action of green coconut water (GCW) on the antiandrogenic effects of flutamide on the sex hormone homeostasis along the hypothalamic pituitary gonadal (HPG) axis and its correlation to the weight distributions of the reproductive organs: testis, epididymis, prostate and seminal vesicle in male peripubertal Wistar rats. Materials and methods: Thirty-six (36) pre-pubertal male Wistar pups at postnatal ages of Postnatal day (PND) 11 were purchased, acclimatized, and randomly distributed at PND 25 into six experimental groups A-F. Group A, B and C received distilled water, flutamide at 25 mg/kg and green coconut water (GCW) at 20 ml/kg respectively for 6 weeks. Group D and E received 25 mg/kg flutamide for 2 weeks then GCW at 10 ml/kg and 20 ml/kg respectively 4 weeks, while Group F received 25 mg/kg flutamide and GCW at 20 ml/kg concomitantly for 6 weeks. At the end of the experiment PND 67, the testis, the epididymis, the prostate, the seminal vesicles, and blood sample were obtained for both morphological and hormonal evaluations. Results: GCW administration significantly revived weight distributions of reproductive organs that were reduced due to the anti-androgenic action of flutamide. More so, GCW significantly increased the concentrations of intratesticular testosterone and follicle stimulating hormone (FSH), while it brings to moderate threshold luteinizing hormone (LH) concentration in flutamide treated peripubertal Wistar rats. There is an evident submission that the increment in reproductive organs' weight correlate with the increase in the sex hormones profiles. Conclusion: The findings from this study suggest that GCW administration may be efficient to restore sex hormone imbalance with corresponding increase in organ weights which underpin many cases of male factor infertility.